Identification of copper precipitates in scrap based recycled low carbon rebar steel. (15th April 2017) - Ramadan, A.; Shash, A.Y.; El-Mahallawi, I.S.; Senk, D.; Mattar, T.
Abstract: This work assesses the effect of increased copper content appearing in recycled steel on the type and morphology of formed precipitates and hence on the steelmaking process and the final product's mechanical properties. The tramp elements (copper, lead and tin) segregate at the grain boundaries as brittle phases leading to reduction in the impact toughness and the ductility. Copper precipitates were found at the grain boundaries and through the grains around manganese sulphides in different morphologies. The chemical composition and shape of these precipitates depend on the cooling rate and other elements as nickel, silicon, sulphur and manganese. The copper precipitates act as brittle phases leading to reduction in the impact toughness and ductility. The potential of the accumulation of the residual copper for both hot rolled and Tempcore processed steel, was assessed. The results show that by applying Tempcore process a more uniform and finer distribution of copper precipitates is formed, with change in their morphology from plate-like to spherical shape. The results also show that the addition of nickel and silicon changes the harmful brittle copper precipitates to a more complex form with the formula NiSiMn(MnCuS)(Cu3 P), which is surrounded by a NiSiMnCu solid solution. Graphical abstract: Highlights: Copper content above 0.36% leads to increase in tensile strength, reduction in impact toughness and in hot ductility. Ellipsoid-form Cu3 P-MnCuS precipitates is responsible for impairing the mechanical properties of copper-containing steel. Addition of nickel and silicon changes the precipitates to be surrounded by a shell of CuNiSiMn solid solution phase. Applying Tempcore changes the precipitates to be spheroid-form Cu3 P-MnS surrounded by a CuMn solid solution shell.